Talent Management dan Konsekuensinya terhadap Employee Engagement dan Employee Retention - Veronika Agustini Srimulyani (Forum Inovasi Bisnis dan Manajemen, 2020)
To gain a competitive advantage, employee engagement is indispensable. Therefore, an effective talent management system is needed in order to increase employee engagement. The aim of this research at knowing talent management at the XYZ Foundation in Madiun City and analyzing the impact of talent management on employee engagement and employee retention. This study also aims to analyze the effect of employee engagement as mediating the relationship of talent management with employee retention. The number of respondents in the study were 69 employees. Data gathered were initially analysed using SPSS version 22.0. From the descriptive analysis, it was found that: 1) employee response to talent management at XYZ Foundation as a whole was high; 2) work engagement on XYZ Foundation was high; 3) employee retention on XYZ Foundation was very high. The results of the hierarchical regression and path analysis indicated that: 1)talent management had a significant positive effect on work engagement; 2) talent management had a significant positive effect on employee retention; 3)work engagement had a significant positive effect on employee retention; 4) work engagement acts as a partial mediation of the influence of talent management on employee retention.